Electrical conductivity of waxes as model systems for polyethylene: Role of water. Issue 22 (30th November 2019) - Hosier, Ian; Vaughan, Alun; Quirke, Nick
ABSTRACT: Novel experimental and theoretical studies of the electrical conductivity of high‐purity dodecane, paraffin wax, and low‐density polyethylene (PE) are reported herein. The role of the charge density, water content, and phase changes in determining conductivity as the temperature increases from 25 to 65 °C, a temperature range relevant to applications of insulating materials, is determined. Low levels of absorbed water determine the measured conductivity for T < 50 °C and this can be explained by taking account of the charge carriers produced by the autoionization of water. In comparison to commercial PE and lubricating oils, the temperature dependence of the conductivity of dry n ‐dodecane is anomalously high. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48765. Abstract : Effect of temperature on the electrical conductivity of the various materials used in this investigation